Targeting Gas6/TAM in cancer cells and tumor microenvironment - Wu, Guiling; Ma, Zhiqiang; Cheng, Yicheng; Hu, Wei; Deng, Chao; Jiang, Shuai; Li, Tian; Chen, Fulin; Yang, Yang (Molecular cancer, 2018)
Growth arrest-specific 6, also known as Gas6, is a human gene encoding the Gas6 protein, which was originally found to be upregulated in growth-arrested fibroblasts. Gas6 is a member of the vitamin K-dependent family of proteins expressed in many human tissues and regulates several biological processes in cells, including proliferation, survival and migration, by binding to its receptors Tyro3, Axl and Mer (TAM). In recent years, the roles of Gas6/TAM signalling in cancer cells and the tumour microenvironment have been studied, and some progress has made in targeted therapy, providing new potential directions for future investigations of cancer treatment. In this review, we introduce the Gas6 and TAM receptors and describe their involvement in different cancers and discuss the roles of Gas6 in cancer cells, the tumour microenvironment and metastasis. Finally, we introduce recent studies on Gas6/TAM targeting in cancer therapy, which will assist in the experimental design of future analyses and increase the potential use of Gas6 as a therapeutic target for cancer.